The Representation of Values of Mutual Cooperation as A Part of Character Education in An English Textbook - Bisma Yudha Mandala; Hanip Pujiati (Lembaga Penelitian dan Pengabdian kepada Masyarakat dan Program Studi Pendidikan Bahasa Inggris Fakultas Bahasa dan Seni Universitas Negeri Jakarta, 2020)
This study aims to analyze all of the written expressions that represent values of mutual cooperation in the English textbook entitled “English in Mind Second Edition (Student’s Book Starter) Special Edition used for seventh graders in Al-Azhar Islamic Junior High Schools in Indonesia and to provide a description regarding to what extent the values of mutual cooperation are encouraged in the textbook. In data collection, content analysis approach was applied following the indicators of values of mutual cooperation from Kemendikbud and other sources. The findings show that (1) 172 expressions are considered having the values of mutual cooperation from six different kinds of values of mutual cooperation, and the most among others is the values of tolerance with the amount of 25% of the total expressions, (2) each of the six different kinds of values of mutual cooperation has different characteristics indicated by keywords, and (3) to some extent, the values of mutual cooperation play a major part that they exist in every section of the materials in the textbook, especially the values of tolerance, and that similar keywords encouraging values of mutual cooperation occur in every section of the textbook.